CONSUMPTION OF OZONE-DEPLETING SUBSTANCES: CONSUMPTION OF OZONE-DEPLETING SUBSTANCES - Daulbayeva, Almira; Filipova, Margarita (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The destruction of the ozone layer, it is an extremely serious problem for mankind. Therefore, a number of international agreements were adopted to reduce the production and use of particularly aggressive halocarbons and finding replacement by other substances. The article describes the trend of consumption of ozone-depleting substances in Kazakhstan over the past fifteen years.